SP4PS: service process rewriting for efficient and proper web services composition. (1st January 2013) - Mekour, M. Mansour; Benslimane, Sidi Mohamed
Web services have become a key technology to implement distributed systems and perform applications' integration. Service composition involves the development of customised services often by discovering, integrating, and executing existing services. This can be done in such a way that already existing services are orchestrated into one or more new services that fit better to the composite application. In this paper, we propose a novel approach to tackle the dynamic services composition problem. Mainly, we focus on service behaviour formalisation to provide a representation that enables us to perform the analysis of service interaction for service behavioural rewriting and combination. Our approach takes advantage of control flows compatibility and service part-consumption to select, integrate and interleave service processes in order to fulfil the provider's constraints and satisfy the requester's needs. The experimental results show that our proposal can contribute to enhance the dynamic user task realisation, and ensure an efficient and proper web service consumption at the provider and the requester's level.